1995
DOI: 10.1175/1520-0477(1995)076<0021:tdbwoj>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Daytona Beach Wave of 3–4 July 1992: A Shallow-Water Gravity Wave Forced by a Propagating Squall Line

Abstract: An unexpected run-up of the ocean along Daytona Beach, Florida, on 3-4 July 1992 was associated with at least one large ocean wave. The wave, which reached a height of about 3 m above normal tide, injured 75 people and damaged property along Daytona Beach. Analyses of meteorological and oceanographic observations are consistent with the hypothesis that a squall line generated a long water wave. The critical evidence is that the propagation speed of the squall line matched the shallow-water wave speed that prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 12 publications
0
47
0
Order By: Relevance
“…In the summer, it is common to observe MCSs with long-lasting squall lines propagating almost parallel to the coastline. The Daytona Beach ''Rogue Wave'' of June 1992 (Churchill et al 1995;Sallenger et al 1995) was an example of a meteotsunami produced by a squall line of a MSC that propagated southward along the East Coast of Florida. Moreover, the extreme weather of the rainy season in this area is also characterized by the formation and passage of tropical cyclones.…”
Section: Types Of Meteorological Conditions That Produced Meteotsunamismentioning
confidence: 99%
See 2 more Smart Citations
“…In the summer, it is common to observe MCSs with long-lasting squall lines propagating almost parallel to the coastline. The Daytona Beach ''Rogue Wave'' of June 1992 (Churchill et al 1995;Sallenger et al 1995) was an example of a meteotsunami produced by a squall line of a MSC that propagated southward along the East Coast of Florida. Moreover, the extreme weather of the rainy season in this area is also characterized by the formation and passage of tropical cyclones.…”
Section: Types Of Meteorological Conditions That Produced Meteotsunamismentioning
confidence: 99%
“…One of the best-known examples of meteotsunamis affecting the East Coast of the USA was the event of Daytona Beach, Florida (July 4, 1992) (Churchill et al 1995;Sallenger et al 1995). The wave had a 3 m height and caused injuries to at least 75 individuals and damage to a dozen vehicles near the beach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies document this shelf as a place where long ocean waves are atmospherically generated (Yankovsky, 2008;Churchill et al, 1995). Both generation and propagation of edge waves along the US coastline have been documented several times during the last 60 yr (Munk et al, 1956;Greenspan, 1956;Beardsley et al, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…An early study by Donn and McGuinness (1960) focused on the effect of 4-10 min air pressure oscillations on the sea level, 80 miles away from New York City. They found that the inverted barometer (Donn and Balachandran, 1960;Churchill et al, 1995;Paxton and Sobien, 1998). Tropical storm and associated long ocean waves have been found to excite onemeter-high sea level oscillations over the coasts of Newfoundland (Mercer et al, 2002;Mecking et al, 2009); both resonantly generated waves and waves reflected/refracted at the shelf edge are found to contribute to the observed coastal sea level oscillations.…”
Section: Introductionmentioning
confidence: 99%